A cyclic thioketone as biradical heterocyclopentane-1, 3-diyl: synthesis, structure and activation chemistry. Issue 11 (27th April 2022) - Beer, Henrik; Linke, Alexander; Bresien, Jonas; Villinger, Alexander; Schulz, Axel
Abstract : Reaction of [( μ -NR)P˙]2 with CSCl2 and Mg gives a deep blue, highly labile cyclic thioketone with singlet biradical character. It can be converted to a housane-type isomer by light and to bicyclic cage compounds by addition of CS2 and benzaldehyde. Abstract : The reaction of the biradical [( μ -NTer)P˙]2 with thiophosgene, SCCl2, leads to a cyclic phospha-aza thiourea derivative in very good yields. This synthetic approach represents a new possibility to prepare cyclic thioketones starting from four-membered cyclo-diphosphadiazanediyls by formal CS insertion with simultaneous oxidation of the two phosphorus atoms by the two chlorine atoms. When the phospha-aza thiourea derivative is reduced with magnesium chips, a deep blue, highly labile cyclic thioketone is formed, which can be regarded as a biradical heterocyclopentane-1, 3-diyl. This new biradical can be converted to a housane species by light, which triggers transannular P–P bond formation. A thermal back-reaction was not observed, but scavenging reactions with CS2 or PhCHO clearly indicate the intermediate formation of the labile, biradical cyclic thioketone. Various intercepted products, such as [2.2.1]bicyclic cage compounds could be isolated and structurally characterized. Freshly in situ generated biradical thioketone can be utilized to activate small molecules.